Preparedness of Traditional Fishermen in Facing Extreme Weather in the Coastal Area of Cermin Beach - Susilawati Susilawati; Salsabila Zahri Sativa; Nabila Fitri; Suci Ramadhani Rangkuti; Fabi Ayyi Afnanin (PROMOTOR, 2026)
Extreme weather poses a serious threat to the safety and activities of traditional fishermen in coastal areas, including Cermin Beach in North Sumatra. This study aims to describe fishermen's knowledge of extreme weather, their preparedness before going to sea, and the challenges they face when sudden weather changes occur. The research method used was qualitative, with in-depth interviews with purposively selected traditional fishermen. The results indicate that most fishermen still rely on natural signs such as clouds, wind, and personal intuition, although some have begun to utilize weather apps or GPS as additional sources of information. Fishermen's preparedness for extreme weather remains relatively low, indicated by the minimal use of safety equipment such as life jackets and the lack of special preparation before going to sea. The decision of some fishermen to continue going to sea despite adverse conditions is also influenced by economic pressures. The main obstacles faced include high waves, strong winds, heavy rain, and a lack of safety facilities on board. These findings emphasize the need for improved safety education, the provision of protective equipment, and the use of official weather information to reduce the risk of accidents at sea.